Anti-diabetic potential of chromium histidinate in diabetic retinopathy rats - Ulas, Mustafa; Orhan, Cemal; Tuzcu, Mehmet; Ozercan, Ibrahim Hanifi; Şahin, Nurhan; Gencoglu, Hasan; Şahin, Kazım (Bmc, 2015)
Background: Chromium (Cr) is commonly used as a complementary medicine for diabetes mellitus. Several studies suggest that Cr intakes may improve glucose metabolism and decrease oxidative stress. Therefore, we aimed to assess the effects of chromium histidinate (CrHis) supplementation using a range of reliable biomarkers of oxidative damage and histopathological changes in rats with diabetic retinopathy. Methods: Diabetes was induced with streptozotocin [(STZ), 55 mg/kg] by intraperitoneal injection in male Long-Evans rats. Three weeks after STZ injection, rats were divided into four groups, namely, untreated normal controls, normal rats receiving CrHis (110 mu g/kg/day); untreated diabetics and diabetics treated with CrHis (110 mu g/kg/day) orally for 12 weeks. Results: In the untreated diabetic group, levels of serum glucose, glycosylated haemoglobin (HbA1c), total cholesterol (TC) and retina malondialdehyde (MDA) were significantly increased, while expressions of retina insulin, and glucose transporter 1 (GLUT 1) and glucose transporter 3 (GLUT3) and level of serum insulin were decreased. CrHis supplementation was found to reduce the levels of glucose, HbA1c, total cholesterol and MDA and to improve the GLUT1, GLUT3 and insulin expressions in STZ-induced diabetic rats. CrHis prevents the changes in the expressions of GLUT1, GLUT3 and insulin and the level of MDA in the retina tissue, confirming the protective effect of CrHis supplementation against the retinopathy caused by STZ. Histopathologic findings suggest that the CrHis-treated diabetic group had normal retinal tissue appearance compared with the untreated diabetic group. Conclusions: These results verify that CrHis has critical beneficial effects against retinal complications. Although detailed studies are required for the evaluation of the exact mechanism of the ameliorative effects of CrHis against diabetic complications, these preliminary experimental findings demonstrate that CrHis exhibits antidiabetic effects in a rat model of diabetic retinopathy by regulating the glucose metabolism and suppressing retinal tissue damage.
Keywords: Diabetes; Chromium; Retinopathy; Glucose transporter proteins; Oxidative stress